2019
DOI: 10.12998/wjcc.v7.i10.1161
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guidance for transforaminal percutaneous endoscopic lumbar discectomy may prevent radiation exposure: A case report

Abstract: BACKGROUND Percutaneous endoscopic lumbar discectomy (PELD) has become a mature and mainstream minimally invasive surgical technique for treating lumbar disc herniation (LDH). Repeated fluoroscopy, with more than 30 shots on average, is inevitable to ensure its accuracy and safety. However, exposure to X-rays may pose a threat to human health. We herein report a case of ultrasound (US)-assisted PELD in two levels of LDH to explore a new possibility that can reduce the radiation dose during puncture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…14,15 Lumbar Oswestry disability index (ODI) is used to score lumbar function and pain, and the higher the OSI score, the more severe the lumbar dysfunction of patients. [16][17][18][19] The results showed that VAS and ODI scores were significantly lower than before treatment, which indicated that the pain and lumbar function of patients with disc herniation were significantly improved after the use of spinal endoscopic nucleus pulposus extraction, which was basically consistent with the research results of Zhang et al 20 Follow-up results showed that there were no perioperative complications such as infection and nerve root injury. In short, the endoscopic resection of the nucleus pulposus for the treatment of disc herniation has excellent neurological safety and is worthy of clinical adoption.…”
Section: Discussionsupporting
confidence: 85%
“…14,15 Lumbar Oswestry disability index (ODI) is used to score lumbar function and pain, and the higher the OSI score, the more severe the lumbar dysfunction of patients. [16][17][18][19] The results showed that VAS and ODI scores were significantly lower than before treatment, which indicated that the pain and lumbar function of patients with disc herniation were significantly improved after the use of spinal endoscopic nucleus pulposus extraction, which was basically consistent with the research results of Zhang et al 20 Follow-up results showed that there were no perioperative complications such as infection and nerve root injury. In short, the endoscopic resection of the nucleus pulposus for the treatment of disc herniation has excellent neurological safety and is worthy of clinical adoption.…”
Section: Discussionsupporting
confidence: 85%
“…However,successful use of ultrasound assistance or real-time guidance to facilitate a di cult interlaminar lumbar puncture for other purposes in patients with spinal fusion instrumentation [21,26,34] has been reported previously. Similarly, the transforaminal lumbar injection technique, which has been used under CT guidance for intrathecal access in patients with spinal fusion where a interlaminar approach is often not possible, has also been reported to be successfully performed with ultrasound guidance in other circumstances [35,36]. Therefore, the value of ultrasound guidance in SMA patients with spinal fusion is worthy of attention and exploration.…”
Section: Limitationsmentioning
confidence: 99%
“…Disc herniation is one of the most common causes of lumbar and leg pain, which can restrict the patient's mobility. 1,2 In severe cases, people are unable to care for themselves in daily life. The most common types of disc herniation are L3/4 and L4/5 herniations.…”
Section: Introductionmentioning
confidence: 99%